FEASIBILITY ANALYSIS OF OPERATION OF PURSE SEINE AS A FISHING VESSEL IN BONE BAY, SOUTH SULAWESI - Andi Imran Anshari (Journal of Agriculture, 2022)
This study aims to analyze the feasibility of operating purse seine vessels operated in Bone Bay. The sampling method uses purposive sampling. There are 4 ship samples and to facilitate measurement using ships that are docking. The data analyzed are the ratio of the main size of the ship, stability, seaworthiness criteria, and ship operation criteria. The results showed that the feasibility of operating purse seine vessels operating in Bone Bay, feasible to operate based on the results of the analysis of each parameter. The L/B ratio value of the purse seine vessels studied ranged from 3.73 – 4.59; L/D ranges from 10.72 – 12.58; and B/D ranges from 2.34 – 3.16. The stability curve of sample ship 1 shows a Max GZ value of 163.27 cm at a slower angle of 73.6 deg, sample ship 2 shows a Max GZ value of 159.75 cm at a low angle of 58.2 deg, sample ship 3 shows a Max GZ value of 154.75 cm at a low angle of 60.9 deg and sample ship 4 Data shows a Max GZ value of 139.59 cm at a low angle of 60.9 deg. The criteria value of the sample ship has met the minimum value standards set by the IMO (International Maritime Organization).